Christian Morals in the Bura Su'a Ritual of Ngada, Flores, Indonesia - Lina, Paskalis; Dou, Josef San (Analisa: Journal of Social Science and Religion, 2025)
Bura su’a is a special ritual performed by the Ngada people in Eastern Indonesia in their main traditional house (Sa'o Ngaza) on the eve of their traditional New Year celebration called Reba. This ritual aims not only to pass on the heritage of their ancestors and important traditional moral values, but also to affirm the existence and identity of the clan. This article aims to examine the moral messages conveyed in the Bura su’a ritual from a Christian moral perspective. Using a descriptive, qualitative, interactive analysis approach and contextual theology methods, the authors will examine this theme in three parts. First, they will discuss research studies of the su’a and the Bura su’a ritual, as well as the symbols and expressions used in it. Second, the authors will examine the Bura su’a ritual from a Christian moral perspective. Here, the authors will compare the messages in the Bura su’a ritual with certain concepts in Christian moral theology. Third, the authors will recommend efforts to ensure the preservation of this ritual in Ngada culture and to concretize the moral message of living together in the digital age. The authors found that the Bura su’a ritual contains Christian moral values, namely, first, respect for God, ancestors, fellow human beings, and nature; second, parental responsibility in educating children and concern for the weakest and poorest in the community; and third, the formation of a morally integrated personality based on biblical and theological virtues of courage, honesty, perseverance, and justice.